Effect of playing position and microcycle days on the acceleration speed profile of elite football players - Antonio Alonso-Callejo; Jorge García-Unanue; Andrés Perez-Guerra; David Gomez; Javier Sánchez-Sánchez; Leonor Gallardo; Jose María Oliva-Lozano; Jose Luis Felipe (Scientific Reports, 2022)
Abstract The aim of this study was to analyse the differences in the A–S profile of elite football players induced by playing position and the microcycle day. Players belonged to a second division club in the Spanish La Liga competition. They were classified into five playing positions: central defenders (CD), full backs (FB), midfielders (MF), wide midfielders (WMF) and forwards (FW). Microcycle days were categorised according to the days until matchday (MD, MD-1, MD-2, MD-3, MD-4 and MD-5). Data was collected along six microcycles, including one match per microcycle. The variables analysed were: maximal theoretical acceleration (A0), maximal theoretical speed (S0), maximal acceleration (ACCmax), maximal speed (Smax) and A–S slope (ASslope). Significant differences were found within positions and microcycle day for all variables (p < 0.05). Match day (MD) showed greater values than the training sessions in A0, ACCmax and Smax (p < 0.05). The highest values for variables associated with acceleration capabilities were found in CD on MD, whereas speed variables were higher in WMF. MD-2 showed the lowest values in all variables except for ASslope. Maximal acceleration and sprint abilities are therefore affected by playing position. Wide positions showed the highest speed capacity, and CD presented a likely acceleration profile. Higher values for all variables concerning the microcycle day, were achieved on MD, and were not reproduced during training with the consequent injury risk and performance decrease it takes.